Beginning ASP.NET 4 in CSharp 2010 - MacDonald, Matthew (Apress, 2012)
ASP.NET is Microsoft’s platform for developing web applications. Using ASP.NET, you can create ecommerce shops, data-driven portal sites, and just about anything else you can find on the Internet. Best of all, you don’t need to paste together a jumble of HTML and script code in order to program the Web. Instead, you can create full-scale web applications using nothing but code and a design tool such as Visual Studio 2008. The cost of all this innovation is the learning curve. To master ASP.NET, you need to learn how to use an advanced design tool (Visual Studio), a toolkit of objects (the .NET Framework), and an objectoriented programming language (such as C# 2010). Taken together, these topics provide more than enough to overwhelm any first-time web developer. Beginning ASP.NET 4 in C# 2010 assumes you want to master ASP.NET, starting from the basics. Using this book, you’ll build your knowledge until you understand the concepts, techniques, and best practices for writing sophisticated web applications. The journey is long, but it’s also satisfying. At the end of the day, you’ll find that ASP.NET allows you to tackle challenges that are simply out of reach on many other platforms.